2016
DOI: 10.1167/iovs.16-19804
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Profiles Qualify Phenotypic Features of Cultured Human Corneal Endothelial Cells

Abstract: PURPOSE. To elucidate a noninvasive method to qualify and identify cultured human corneal endothelial cells (cHCECs) devoid of cell-state transition and adaptable for cell-based therapy.METHODS. The variations of cHCECs in their composition of heterogeneous subpopulations (SPs) were verified in relation to their surface cluster-of-differentiation (CD) markers and their morphology. The profiles of microRNA (miRNA) in cultured cells or supernatants were detected by 3D-Gene Human microRNA Chips (Toray Industries,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 27 publications
(25 reference statements)
0
17
0
Order By: Relevance
“…31 Furthermore, miR34a detection in culture medium was linked to a lack of CD44 expression and thus to the absence of aneuploidy. 32 Although miRNA analysis shows some potential for use in the validation of cell therapy products, we are concerned about the concomitant isolation of miRNAs from the fetal bovine serum and mesenchymal stem cell–conditioned medium that are used as additives in their cell culture medium. 33,34…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Furthermore, miR34a detection in culture medium was linked to a lack of CD44 expression and thus to the absence of aneuploidy. 32 Although miRNA analysis shows some potential for use in the validation of cell therapy products, we are concerned about the concomitant isolation of miRNAs from the fetal bovine serum and mesenchymal stem cell–conditioned medium that are used as additives in their cell culture medium. 33,34…”
Section: Resultsmentioning
confidence: 99%
“…18,2830 The unique phenotypic markers that have reportedly been found to be linked to healthy HCEnCs in these studies are CD166, CD200, GPC4, HLA-ABC, and PD-L1. 21,32,40,41 In addition to markers that positively identify HCEnCs, attention should also be paid to the absence of certain gene or protein expressions, in particular α-SMA, CD9, CD24, CD26, CD44, CD73, CD90, CD105, and CD133 for phenotypic studies, and Snail, ZEB1, and vimentin, which have been shown to be negative in HCEnCs. 19,3235 Nevertheless, these markers are challenged (i.e., CD166 20 ) and have not been widely adopted by other groups to date.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that the only miR capable of discriminating CD44 À effector cells from CD44 þþ -CD44 þþþ SPs was identified as miR34a. 35 Consequently, it is conceivable that in the previous experiment of Koizumi et al, 40 either CD44 þþþ or CD44 þþ SPs with downregulated miR34a used the RhoA/MMP2 pathway activated in the undifferentiated SPs. 33 If this assumption is correct, FIGURE 2.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we confirmed the upregulation of miR29 in parallel with that of CD44 expression among distinct SPs, as our findings showed that miR29 was most downregulated in effector cells with a CD44-phenotype among cHCEC SPs. 35 Interestingly, miR29 reportedly has an EMT-promoting effect. 36 Reportedly, TGF-b can initiate and maintain the EMT in various biological and pathologic systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation